Salt tolerance of mesquite - W Jarrell; R Virginia (California Agriculture, 1984)
Not available – first paragraph follows: California's native mesquite grows primarily in areas of shallow ground water where temperatures are rarely below 24°F. Many of these areas have naturally occurring saline surface or subsurface soils — up to 88 dS/m (about 56,300 mg/L) in the saturation extract. Root systems of mesquite, including the native species, Prosopis glandulosa var. torreyana, are well adapted for growth in areas where the plant must rely primarily on ground water. Another species, Prosopis tama-rugo, native to the Atacama Desert of Chile, where average annual rainfall is less than Vi inch, relies wholly on groundwater derived from snow and rain in the Andes Mountains.